Recovery and exit of zombie firms in Portugal: A remake - Carlos Carreira; Paulino Teixeira; Ernesto Nieto-Carrillo (Aussenwirtschaft, 2023)
Encouraged by the forbearance of creditors and exit barriers (e.g., inefficient insolvency regimes), the zombie phenomenon has weakened business dynamism and, as a consequence, has slowed economic growth in most economies in recent decades. In this paper, we examine the recovery and exit of zombie firms, as well as the determinants of these transitions. Based on a panel of Portuguese firms' population covering the period 2004-2020, we find a widespread prevalence of zombie firms, which are relatively less productive than non-zombies. Moreover, industries with a higher share of zombies have lower productivity levels. Finally, we find that the probability of transition into recovery and exit is relatively small. However, operational and technological restructuring, as well as financial restructuring, are shown to be key drivers of zombie firms' recovery. The insolvency environment is also found to be a strong factor in stimulating business restructuring.
Keywords: D24; G32; G33; L25; O47; 330; zombie firms; exit; recovery; restructuring; downsizing